2019
DOI: 10.1136/bmjopen-2018-024800
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of Chou-Ling-Dan granules in the treatment of seasonal influenza via combining Western and traditional Chinese medicine: protocol for a multicentre, randomised controlled clinical trial

Abstract: IntroductionChou-Ling-Dan (CLD) (Laggerapterodonta) granules are an ethnic herbal medicine from Yunnan province of China. CLD granules have been used for the treatment of inflammatory conditions and feverish diseases in China, including seasonal influenza, but few evidence-based medicine (EBM) clinical studies have been conducted to assess its efficacy and safety in the treatment of influenza. Here, we performed an EBM clinical trial combining Western Chinese medicine and traditional Chinese medicine (TCM) eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Among them, Lianhua Qingwen granules, Xiaoer Resuqing granules, and Xiaoer Shuanghuanglian mixture use Lonicera japonica (Thunb) and Forsythia suspensa (Thunb, Vahl) In future clinical practice, combination medications may provide new ideas to treat children with influenza, promoting the use of CPMs and TCM for this purpose (Ru et al, 2017;Gao and Wang, 2018;Liu et al, 2019). They are especially effective at shortening the time to fever resolution and relieving the symptoms of influenza Duan et al, 2011;Wang et al, 2011;He et al, 2019;Yoshino et al, 2019). This is consistent with the conclusions of the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Among them, Lianhua Qingwen granules, Xiaoer Resuqing granules, and Xiaoer Shuanghuanglian mixture use Lonicera japonica (Thunb) and Forsythia suspensa (Thunb, Vahl) In future clinical practice, combination medications may provide new ideas to treat children with influenza, promoting the use of CPMs and TCM for this purpose (Ru et al, 2017;Gao and Wang, 2018;Liu et al, 2019). They are especially effective at shortening the time to fever resolution and relieving the symptoms of influenza Duan et al, 2011;Wang et al, 2011;He et al, 2019;Yoshino et al, 2019). This is consistent with the conclusions of the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Data will be collected from the dysmenorrhea daily of symptoms recorded by participants, the CRF tables, and TCM syndrome scores recorded by the trial team [31]. All patients will be invited to answer the data administrator's self-administered electronic questionnaire [32].…”
Section: Data Collection and Managementmentioning
confidence: 99%
“…Also, Across-sectional study conducted in the Central Appalachian Region showed that Trigonella foenum-graecum L. was regularly used in treating Influenza (Alwhaibi et al, 2017). More and more RCTs are focusing on the efficacy and safety of combination use of TCM and conventional therapy (He et al, 2019). In summary, there is potential value in using TCM to treat influenza among children and pregnant women; nevertheless, more investigations are necessary for clinical validations.…”
Section: Use Of Tcm In Treating Influenza Among Children and During Pmentioning
confidence: 99%
“…Therefore, these challenges call for more effort and attention toward developing fresh strategies to combat influenza. Previously, TCM demonstrated a positive anti-viral effect on influenza virus and alleviated the symptoms among patients (He et al, 2019;Nagai et al, 2019). In TCM theory, influenza disease was classified as "YI Disease" and was first reported in Huang Di Nei Jing.…”
Section: Introductionmentioning
confidence: 99%